Penilaian Status Sumberdaya Ikan Hasil Tangkapan Dominan yang Didaratkan di PPI Kedonganan dengan Pendekatan Multi-Criteria Analysis (MCA) - Ayu Pratiwi, Made; Ernawati, Ni Made; Wijayanti, Ni Putu Putri (Journal of Marine and Aquatic Sciences; Vol 6 No 2 (2020)DO - 10.24843/jmas.2020.v06.i02.p1, 2020)
Fishes are an open access resource so that monitoring of fishing in the sea is very difficult. It is feared will lead to overfishing which eventually led to a drastic reduction in fish stocks in nature. So that people will be faced with the problem of scarcity of fish resources. One of the fish landing sites in Bali is Pangkalan Pendaratan Ikan (PPI) Kedonganan located in Fishery Management Area of Republic Indonesia (WPP-RI) 713. Therefore, it is necessary to understanding the current status of fish resources is very important in order to be a strong foundation in the management fisheries in PPI Kedonganan. The study was conducted by assessing five indicators of fish resources (fish size, yuwana fish, species composition, range collapse, and ETP species) by establishing a set of criteria, scores and weights and analyzed by multi-criteria analysis (MCA) approach. There found 16 species of catch fish with Cob Fish as dominant catch fish (54%). The trend of changes in fish size has increased significantly by + 90.18% of the initial length (Indicator of fish size). An average of 99% of fish catched were the target fish (Indicator of species composition). An average of 28.33% of fish catches included yuwana fish (Indicator of yuwana fish proportion). The results of interviews, it was found that 73% of fishermen state that fishing areas increasingly difficult from year to year (Indicator ranges collapse). There were <20% of fish catches including protected species (Scomberomorus commerson and Sphyrna lewini). It is also supported based on fisherman interview data that there were still protected fish such as turtles, sharks and rays that are caught but in small quantities (Indicator of ETP fish species). The result of composite analysis showed that the status of fish resources in Kedonganan was still very good with composite value of 86.1.